2021
DOI: 10.1021/acsami.1c01024
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free, Graphene Oxide-Based Tunable Soliton and Plasmon Engineering for Biosensing Applications

Abstract: The quest for auxiliary plasmonic materials with lossless properties began in the past decade. In the current study, a unique plasmonic response is demonstrated from a stratified high refractive index (HRI)–graphene oxide (GO) and low refractive index (LRI)–polymethyl methacrylate (PMMA) multistack. Graphene oxide plasmon-coupled emission (GraPE) reveals the existence of strong surface states on the terminating layer of the photonic crystal (PC) framework. The chemical defects in GO thin film are conducive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
132
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(142 citation statements)
references
References 71 publications
10
132
0
Order By: Relevance
“…While the surface enhanced resonance Raman scattering (SERRS) platform supported by Ag nanowires as a plasmonic substrate could lower the detection limit to nanomolar levels, 65 our earlier work using the SPCE platform lowered the detection limit to 0.1 picomolar concentrations using AgCD (silver decorated carbon dots) as efficient nanoantennas in the SPCE platform. 18 Nevertheless, there are no reports that discuss further lowering this detection limit. In this context, we have engineered the ext.…”
Section: Soluplus Mediated Aunps: Spce Nanointerfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…While the surface enhanced resonance Raman scattering (SERRS) platform supported by Ag nanowires as a plasmonic substrate could lower the detection limit to nanomolar levels, 65 our earlier work using the SPCE platform lowered the detection limit to 0.1 picomolar concentrations using AgCD (silver decorated carbon dots) as efficient nanoantennas in the SPCE platform. 18 Nevertheless, there are no reports that discuss further lowering this detection limit. In this context, we have engineered the ext.…”
Section: Soluplus Mediated Aunps: Spce Nanointerfacesmentioning
confidence: 99%
“…7−11 The near-field optical confinement provided by the plasmonic NPs generate regions of intense EM "hotspots", when coated on a metal thin film. 16,17 Although a variety of NPs including low-dimensional materials, 18 self-assembled soret colloids, 7 and intermetallics 19,20 have been studied for their photoplasmonic contribution to SPCE, physicochemical evaluation of gold (Au) NPs has been inadequate on account of inevitable quenching of fluorophores located in distances <5 nm. In comparison to other coinage NPs (Ag, Pt, Pd), AuNPs exhibit manifold functionalities due to high stability with precise geometries, extraordinary optoelectronic properties, superior biocompatibility, tunable biophysicochemical properties and ability for multifunctionalization with inorganic/ biological/organic ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the discussed studies, in 2021, Ramamurthy's group [324] engineered a metal-free plasmonic Tamm-resonant metastructure based on a combination of high refractive index graphene-oxide and low refractive index PMMA layers (Figure 10j). From the technical standpoint, it is demonstrated that the realized graphene-oxide plasmon-coupled emission (GraPE) exhibits the presence of robust surface resonances on the terminating layer of the tailored configuration, in which pronounced plasmon hybridization took place across the PMMA stack owing to the chemical defects in the graphene oxide monolayer.…”
Section: Tamm Modes Metasensorsmentioning
confidence: 99%
“…The insets in each panel represent a linear relationship in bilogarithmic coordinates. j-n) Reproduced with permission [324]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%